Penerapan Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Terhadap Hasil Belajar Mata Pelajaran Kerja Bangku Siswa kelas X semester 1 SMK Piri 1 Yogyakarta Tahun Ajaran 2014/2015 - Fauzie Khorniawan; Arief Bintoro Johan (Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of research to find out the results of class X student of SMK Piri 1 Yogyakarta Semester 1 2014/2015 academic year using cooperative learning model Numbered Head Together (NHT). In a comparative study to determine the results of class X class students of SMK Piri 1 Yogyakarta between TP 1 and TP 2 by using cooperative learning model and conventional learning.Descriptive research results indicate student learning outcomes between experimental and control classes classes before their treatment an average value of 5.7 while the experimental class posttest control class 4.8. After an average value treatment experimental classes and control classes had increased to 7.3 while the experimental class to control class 5.4. Of hypothesis test using the self-obtained results of pre-test Thitung< T tabel=1,148 <2.037 with significance level of 5%. Results posttest price Thitung> Ttabel = 2,434 >2.037 with significance level of 5%. There is an increase in Thitung> Ttabel = 2.268 >2.037 with significance level of 5%. Hypothesis test with criteria reject Ho and Ha received.Â